The role of the Arctic in future global petroleum supply - Lars Lindholt; Solveig Glomsrød (Statistics Norway, Research Department, 2011)
The Arctic has a substantial share of global petroleum resources, but at higher costs than in most other petroleum provinces. Arctic states and petroleum companies are carefully considering the potential for future extraction in the Arctic. This paper studies the oil and gas supply from 6 arctic regions during 2010-2050 along with global economic growth and different assumptions regarding petroleum prices and resource endowments. Supply is calculated based on a global model of oil and gas markets. The data on undiscovered resources for the Arctic is based on the estimates by USGS. Sensitivity studies are carried out for two alternative price scenarios and for a 50 per cent reduction of arctic undiscovered resources compared with the USGS 2008 resource estimate. Although a major part of the undiscovered arctic petroleum resources is natural gas, our results show that the relative importance of the Arctic as a world gas supplier will decline, while its importance as a global oil producer may be maintained. We also show that less than full access to undiscovered oil resources will have minor effect on total arctic oil production and a marginal effect on arctic gas extraction. The reason is that Arctic Russia is an important petroleum producer with a sufficiently large stock of already discovered resources to support their petroleum production before 2050.
Keywords: Q31; Q41; R10; 330; Arctic; oil market; gas market; equilibrium model